2022
DOI: 10.1111/bjd.21700
|View full text |Cite
|
Sign up to set email alerts
|

Teprotumumab as a novel treatment for pretibial myxoedema

Abstract: 2 weeks, both in percentage change and in absolute value of the change.Ixekizumab induced immediate improvement in inflammatory markers in patients with GPP with systemic inflammation. This indicates that ixekizumab is a good treatment option for patients in the acute phase or in a flare of GPP, and that its effectiveness can be expected after a few days. Although BT seemed to decrease 1 day after initiation of ixekizumab, no significant difference was observed. The use of antipyretics may have affected the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…A similar mechanism may effect thyroid dermopathy; several previous reports demonstrate response of dermopathy to IGF-1R inhibition. 5 , 6 , 7 , 8 Our patient had preexisting peripheral edema diagnosed as a component of Hashimoto thyroiditis which severely worsened during the Graves episode. While the characterization of this worsening edema is incomplete in the absence of formal dermatologic and radiographic evaluation, photographic documentation is presented.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A similar mechanism may effect thyroid dermopathy; several previous reports demonstrate response of dermopathy to IGF-1R inhibition. 5 , 6 , 7 , 8 Our patient had preexisting peripheral edema diagnosed as a component of Hashimoto thyroiditis which severely worsened during the Graves episode. While the characterization of this worsening edema is incomplete in the absence of formal dermatologic and radiographic evaluation, photographic documentation is presented.…”
Section: Discussionmentioning
confidence: 86%
“…Case reports have demonstrated response of thyroid dermopathy to the standardized dosing regimen. 5 , 6 , 7 , 8 We present a case of rapid improvement in symptoms of TED and amelioration of worsening peripheral edema and acropathy (not to be confused with acropachy) after treatment with teprotumumab.…”
Section: Introductionmentioning
confidence: 96%
“…Topical and intralesional steroids may be beneficial for mild PTM but are not consistently successful in preventing PTM progression . Case reports and series have shown that teprotumumab, an inhibitor of the insulinlike growth factor 1 receptor, is effective in improving PTM . However, teprotumumab has high cost and low availability in some countries, including China; thus, economical and effective treatments are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Several other publications were excluded from further review based on irrelevance to our study topic. [21][22][23] This search method resulted in 3 clinical trials, 2 observational studies, 1 cohort, 6 individual case reports, and 3 case series included in this literature review for further data collection.…”
Section: Methodsmentioning
confidence: 99%